Titanium-containing bottoming nanometer film layer sample wafer and preparation method thereof

The metal substrate is removed through electrochemical reactions and the titanium-containing base nano film layer is retained on the insulating reference sheet, which solves the problem of difficulty in separation and analysis of nano film layers in the prior art, and achieves comprehensive observation and testing of abnormalities at the bottom of the film layer, avoiding the film layer breakage caused by grinding.

CN119510084APending Publication Date: 2025-02-25NANOFILM VACUUM COATING SHANGHAI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411685970.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively separate and analyze the titanium-containing base nanofilm layer, and the film layer is uneven due to particulate matter during the coating process, making it difficult to conduct comprehensive observation and testing through cross-sectional samples.

Method used

By tightly bonding the insulating reference sheet to the surface of the titanium-containing base nanofilm layer and exposing the metal substrate, the metal substrate is removed by electrochemical reaction, thereby retaining the nanofilm layer on the reference sheet to form a sample sheet of the titanium-containing base nanofilm layer.

Benefits of technology

A comprehensive and accurate observation and testing of abnormalities at the bottom of the film layer is achieved, which avoids the film layer breakage caused by grinding and simplifies the sample preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510084A_ABST
    Figure CN119510084A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium-containing bottoming nano-film layer sample wafer and a preparation method thereof, and the method comprises the steps: providing a test piece which comprises a titanium-containing bottoming nano-film layer plated on the surface of a metal substrate; an insulating reference sheet is tightly attached to the surface, away from the metal base material, of the titanium-containing bottoming nanometer film layer; and removing the metal base material from the test piece through a reaction, so that the titanium-containing bottoming nano film layer is reserved on the reference sheet, and the surface, close to the metal base material, of the titanium-containing bottoming nano film layer is exposed, and a titanium-containing bottoming nano film layer sample sheet is obtained and can be further used for researching film layer defects and carrying out related performance tests. The method is simple, easy to implement, low in cost and suitable for application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating sample preparation, in particular to a titanium-containing primer nano-film layer sample and a preparation method thereof. Background Art

[0002] Titanium or titanium alloy is often used as a primer material when coating on a metal substrate with high chemical activity such as iron, zinc, chromium, etc., and can form a single-layer or multi-layer nano film structure containing titanium primer on the surface of the metal substrate. When it is necessary to perform relevant analysis and detection on the titanium primer nano film layer formed on the metal substrate, it is generally carried out by preparing a cross-section sample (slice sample) of the titanium primer nano film layer. Since there is currently no better method for separating the titanium primer nano film layer from the metal substrate, it must be prepared into a sample together with the metal substrate.

[0003] During the coating process, sometimes some particles appear at the bottom of the titanium-containing primer film, resulting in the problem that the final film surface is not flat and smooth enough. However, since these particles are relatively small and difficult to obtain, it is difficult to comprehensively and accurately observe and test the abnormal particles at the bottom of the film through the prepared sample section during failure analysis. In addition, when the prepared sample is cross-sectioned, since there is often a large difference in grinding rate between the metal substrate and the titanium-containing primer nanofilm material, for some film structures with high brittleness that are not suitable for grinding and polishing, the sample preparation failure caused by the film breaking due to grinding is prone to occur. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a titanium-containing primer nanofilm layer sample and a preparation method thereof.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] The present invention provides a method for preparing a titanium-containing primer nanofilm layer sample, comprising:

[0007] Providing a test piece, the test piece comprising a titanium-containing primer nanofilm layer plated on a surface of a metal substrate;

[0008] The insulating reference sheet is closely attached to the surface of the titanium-containing primer nanofilm layer away from the metal substrate;

[0009] The metal substrate is removed from the test piece by reaction, so that the titanium-containing primer nanofilm layer remains on the reference piece and the surface of the titanium-containing primer nanofilm layer close to the metal substrate is exposed to obtain a titanium-containing primer nanofilm layer sample.

[0010] Furthermore, the metal substrate comprises a conductive metal or metal alloy, and the chemical activity of the metal substrate is higher than the chemical activity of the titanium in the titanium-containing base nanofilm layer.

[0011] Furthermore, the metal substrate includes at least one of iron, magnesium, aluminum, zinc, tin, manganese, nickel, chromium or an alloy thereof, and the titanium-containing base nanofilm layer includes a single-layer or multi-layer nanofilm layer with titanium or titanium alloy as the base layer.

[0012] Furthermore, the titanium content in the titanium alloy is greater than 30%, and the titanium alloy does not contain other active metals with higher chemical activity than titanium.

[0013] Furthermore, the removing of the metal substrate from the specimen by reaction specifically includes:

[0014] dissolving sulfuric acid and sulfate in deionized water to obtain a reaction solution;

[0015] The metal substrate on the test piece connected to the positive electrode of direct current and attached with the reference sheet is used as an anode, and the platinum electrode connected to the negative electrode of direct current is used as a cathode, and placed in the reaction solution;

[0016] A voltage is applied between the anode and the cathode, so that the metal substrate reacts with the reaction solution and is dissolved and removed from the test piece.

[0017] Furthermore, the voltage is smaller than a voltage required for the titanium-containing primer material in the titanium-containing primer nanofilm layer to react with the reaction liquid.

[0018] Furthermore, the method for applying a voltage between the anode and the cathode specifically includes: setting a range of the voltage, and applying the voltage in a manner of gradually decreasing the voltage value within the range of the voltage during the entire reaction stage, so that the reaction rate of the metal substrate and the reaction liquid decreases from high to low.

[0019] Furthermore, the method for applying a voltage between the anode and the cathode specifically includes: setting a range of the voltage, and applying the voltage within the range of the voltage in a manner of gradually increasing and then gradually decreasing the voltage value during the entire reaction stage, so that the reaction rate of the metal substrate and the reaction liquid increases from low to high and then to low.

[0020] Furthermore, it also includes: in the entire reaction stage, the pH value and sulfate concentration of the reaction solution are analyzed; when the analyzed pH value exceeds a threshold value, sulfuric acid is added to the reaction solution according to a set sulfuric acid concentration range so that the pH value falls back into the threshold value; when the analyzed sulfate concentration exceeds the lower limit of the set sulfate concentration range, sulfate is added to the reaction solution so that the sulfate concentration reaches the median of the set sulfate concentration range or the initial preparation concentration of sulfate.

[0021] Furthermore, the threshold is less than 2.

[0022] Furthermore, the sulfuric acid concentration ranges from 1.5 to 20 g / L, and the sulfate concentration ranges from 5 to 100 g / L.

[0023] Furthermore, the sulfuric acid concentration ranges from 2 to 12 g / L, and the sulfate concentration ranges from 16 to 80 g / L.

[0024] Furthermore, the voltage range is 2 to 7 V, and the current density applied to the anode ranges from 150 to 700 A / m 2 .

[0025] Furthermore, the sulfate includes at least one of sodium sulfate, potassium sulfate and ammonium sulfate.

[0026] Furthermore, the insulating reference plate is tightly attached to the surface of the titanium-containing base nanofilm layer away from the metal substrate, and the method specifically includes: tightly bonding the reference plate to the surface of the titanium-containing base nanofilm layer away from the metal substrate by an insulating adhesive, and when bonding, first evenly applying the adhesive on the surface of the titanium-containing base nanofilm layer, and then bonding the reference plate to the surface of the titanium-containing base nanofilm layer coated with the adhesive, and using the dead weight of the reference plate to tightly attach the reference plate to the test piece; and, after the reference plate and the test piece are firmly bonded, placing the test piece in the reaction solution.

[0027] Further, the adhesive includes glue or instant adhesive; and / or the reference sheet includes a plastic sheet.

[0028] Furthermore, it also includes:

[0029] Visually observe, and when the metal substrate is dissolved to the target position, cut off the power supply;

[0030] Taking the test piece out of the reaction solution and soaking and cleaning it in pure water;

[0031] The cleaned test piece was air-dried.

[0032] The present invention also provides a titanium-containing base nanofilm layer sample prepared using the above-mentioned method for preparing a titanium-containing base nanofilm layer sample, wherein the titanium-containing base nanofilm layer sample is used to directly observe and test the exposed surface of the titanium-containing base nanofilm layer close to the metal substrate retained on the reference film after the metal substrate is reactively removed, and / or is used to further prepare slice samples.

[0033] It can be seen from the above technical scheme that the present invention first adheres an insulating reference sheet to the surface of the titanium-containing primer nanofilm layer on the test piece to expose the metal substrate, and then removes the metal substrate from the test piece through reaction to obtain a titanium-containing primer nanofilm layer retained on the target area of ​​the reference sheet, which can be further used to study film defects and conduct related performance tests, so as to achieve comprehensive and accurate observation and testing of abnormalities at the bottom of the film layer. At the same time, since there is no metal substrate on the sample, when it is further used to prepare sliced ​​samples, it also effectively avoids the problem of sample preparation failure caused by the large difference in grinding rate between the metal substrate and the nanofilm material, which is prone to occur for some film materials with higher brittleness due to film breakage caused by grinding. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The present invention is a flow chart of a method for preparing a titanium-containing primer nanofilm layer sample.

[0035] Figure 2 A preferred embodiment of the present invention adopts Figure 1 Schematic diagram of the specific steps for preparing a titanium-containing primer nanofilm layer sample.

[0036] Figure 3 This is a schematic diagram of a preferred embodiment of the present invention for removing a metal substrate from a test piece by reaction.

[0037] Figure 4 This is a state diagram of a metal substrate before and after reaction removal according to Example 1 of the present invention. Figure 4 (a) before reaction, Figure 4 (b) after the reaction.

[0038] Figure 5 To adopt Figure 4 Schematic diagram of the film structure comparison of the sliced ​​samples prepared from the specimens before and after the reaction. Figure 5 (a) before reaction, Figure 5 (b) after the reaction.

[0039] Figure 6 This is a state diagram of a specimen before and after the metal substrate is removed by reaction according to the second embodiment of the present invention. Figure 6 (a) before reaction, Figure 6 (b) after the reaction.

[0040] Figure 7 To adopt Figure 6 Schematic diagram of the film structure comparison of the sliced ​​samples prepared from the specimens before and after the reaction. Figure 7 (a) before reaction, Figure 7 (b) after the reaction.

[0041] Figure 8 This is a state diagram of a metal substrate before and after reaction removal according to the third embodiment of the present invention. Figure 8 (a) before reaction, Figure 8 (b) after the reaction.

[0042] Fig. 9 To adopt Figure 8 Schematic diagram of the film structure comparison of the sliced ​​samples prepared from the specimens before and after the reaction. Fig. 9 (a) before reaction, Fig. 9 (b) after the reaction.

[0043] Fig.10 This is a state diagram of a metal substrate before and after reaction removal according to the fourth embodiment of the present invention. Fig.10 (a) before reaction, Fig.10 (b) after the reaction.

[0044] Fig.11 To adopt Fig.10 Schematic diagram of the film structure comparison of the sliced ​​samples prepared from the specimens before and after the reaction. Fig.11 (a) before reaction, Fig.11 (b) after the reaction.

[0045] Fig.12 This is a state diagram of a metal substrate before and after reaction removal according to Example 5 of the present invention. Fig.12 (a) before reaction, Fig.12 (b) after the reaction.

[0046] Fig.13 To adopt Fig.12 Schematic diagram of the film structure comparison of the sliced ​​samples prepared from the specimens before and after the reaction. Fig.13 (a) before reaction, Fig.13 (b) after the reaction.

[0047] Fig.14 This is a state diagram of a specimen before and after the metal substrate is removed by reaction according to Example 6 of the present invention. Fig.14 (a) before reaction, Fig.14 (b) after the reaction.

[0048] Fig.15 To adopt Fig.14 Schematic diagram of the film structure comparison of the sliced ​​samples prepared from the specimens before and after the reaction. Fig.15 (a) before reaction, Fig.15 (b) after the reaction.

[0049] Fig.16 This is a state diagram of a metal substrate before and after reaction removal in Example 7 of the present invention. Fig.16 (a) before reaction, Fig.16 (b) after the reaction.

[0050] Fig.17 To adopt Fig.16 Schematic diagram of the film structure comparison of the sliced ​​samples prepared from the specimens before and after the reaction. Fig.17 (a) before reaction, Fig.17 (b) after the reaction.

[0051] Fig.18 This is a state diagram of a metal substrate before and after reaction removal in comparative example 1. Fig.18 (a) before reaction, Fig.18 (b) after the reaction.

[0052] Fig.19 This is a state diagram of a metal substrate before and after reaction removal in comparative example 2. Fig.19 (a) before reaction, Fig.19 (b) after the reaction.

[0053] Fig. 20 This is a state diagram of a metal substrate before and after reaction removal in comparative example 3. Fig. 20 (a) before reaction, Fig. 20 (b) after the reaction.

[0054] Fig.21 This is a state diagram of a metal substrate before and after reaction removal in Comparative Example 4. Fig.21 (a) before reaction, Fig.21 (b) after the reaction.

[0055] Fig. 22 This is a state diagram of a metal substrate before and after reaction removal in comparative example 5. Fig. 22 (a) before reaction, Fig. 22 (b) after the reaction. DETAILED DESCRIPTION

[0056] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.

[0057] refer to Figure 1 The method for preparing a titanium-containing primer nanofilm sample of the present invention comprises:

[0058] Providing a test piece, the test piece comprising a titanium-containing primer nanofilm layer plated on a surface of a metal substrate;

[0059] The insulating reference sheet is closely attached to the surface of the titanium-containing primer nanofilm layer away from the metal substrate;

[0060] The metal substrate is removed from the test piece by reaction, so that the titanium-containing primer nanofilm layer remains on the reference piece and the surface of the titanium-containing primer nanofilm layer close to the metal substrate is exposed to obtain a titanium-containing primer nanofilm layer sample.

[0061] Wherein, the titanium-containing primer nanofilm layer plated on the surface of the metal substrate includes a single layer or multiple layers of nanofilm layers, and the titanium-containing primer nanofilm layer includes a single layer or multiple layers of nanofilm layers with titanium or titanium alloy as the primer layer. That is, the titanium-containing primer nanofilm layer can be a single layer of titanium or titanium alloy primer layer, or a nanofilm layer with a multiple layers of structure in which other films are plated on the titanium or titanium alloy primer layer. The entire nanofilm layer is combined with the surface of the metal substrate by using titanium or titanium alloy as the primer layer, which can improve the bonding force between the entire nanofilm layer and the surface of the metal substrate, achieve good protection of the surface of the metal substrate, and improve the comprehensive performance of the metal substrate with the titanium-containing primer nanofilm layer. However, this also brings difficulties to the preparation of cross-section samples of the titanium-containing primer nanofilm layer and the relevant analysis and detection of the titanium-containing primer nanofilm layer. In particular, in view of the problem that some particles appear at the bottom of the titanium-containing primer film during the coating process, resulting in the final film surface being not flat and smooth enough, when preparing cross-section samples, these particles are relatively small and difficult to obtain. Therefore, when conducting failure analysis, it is difficult to comprehensively and accurately observe and test the abnormalities at the bottom of the film through the prepared sample cross section. In addition, when the cross-section of the prepared multi-layer nano-film layer samples is ground, due to the large difference in grinding rate between the metal substrate and the nano-film layer material, for some film layer materials in the multi-layer nano-film layer that are more brittle and not suitable for grinding and polishing, it is often easy to cause the film layers to break due to grinding, resulting in sample preparation failure.

[0062] The present invention firstly adheres the insulating reference sheet to the surface of the titanium-containing bottoming nano film layer on the test piece, and exposes the metal substrate, and then removes the metal substrate from the test piece by reaction, so as to obtain the titanium-containing bottoming nano film layer retained on the target area of ​​the reference sheet, which can be further used to study film defects and perform relevant performance tests. For example, by adopting the preparation method of the titanium-containing bottoming nano film layer sample of the present invention, the metal substrate is reacted and removed from the test piece to obtain the titanium-containing bottoming nano film layer sample, and the abnormality occurring at the bottom of the film layer can be observed and tested comprehensively and accurately by directly observing the bottom of the film layer, so as to facilitate failure analysis research. It can also be used to measure some nano film layers with high brittleness that are not suitable for preparing cross-section samples by grinding and polishing. Since there is no metal substrate on the sample, when it is further used to prepare the sliced ​​sample, it can effectively avoid the problem that there is a large difference in grinding rate between the metal substrate and the nano film layer material in the past, and for some film layer materials with high brittleness, it is easy to cause the film layer to break due to grinding and cause the sample preparation failure to occur.

[0063] In some embodiments, the metal substrate includes a conductive metal or metal alloy, and the chemical activity of the metal substrate is higher than the chemical activity of the titanium of the base layer of the titanium-containing base nanofilm layer. By utilizing the characteristic that the chemical activity of the substrate metal is higher than the chemical activity of the titanium of the base layer, the metal substrate can be dissolved and removed from the test piece by causing the metal substrate to react preferentially with respect to titanium, thereby obtaining the titanium-containing base nanofilm layer retained on the target area of ​​the reference film (referring to the area that meets the test requirements and the area at the specified position).

[0064] In some embodiments, the metal substrate includes a highly chemically active conductive metal such as iron, magnesium, aluminum, zinc, tin, manganese, nickel, chromium, or an alloy formed by the above metal elements as the main component. For example, the metal substrate includes ordinary steel, stainless steel, magnesium-aluminum alloy, zinc-magnesium alloy, copper-zinc alloy, tin-lead alloy, nickel alloy, etc. The metal substrate affects the reaction experiment time. Under the same conditions, the higher the activity of the selected metal substrate, the shorter the experiment time.

[0065] In fact, any conductive metal material that has a higher chemical activity than titanium and can react preferentially than titanium can be used as the metal substrate of the present invention.

[0066] In some embodiments, when a titanium alloy is used as the base layer of the nanofilm layer, the titanium content in the titanium alloy needs to be greater than 30% (mass fraction), and the titanium alloy does not contain other active metals with higher chemical activity than titanium. The titanium base layer material or the titanium alloy base layer material may contain elements such as silicon, carbon, and nitrogen.

[0067] In some embodiments, the reference sheet comprises a plastic sheet.

[0068] In some embodiments, the reference sheet material includes acrylic or polypropylene, that is, the reference sheet includes an acrylic reference sheet or a polypropylene reference sheet.

[0069] In some embodiments, the reference sheet has a certain degree of brittleness and can be broken brittlely to form a clear cross section, which is convenient for subsequent cross section processing of the sample, but will not affect the cross section grinding and polishing.

[0070] In some embodiments, the thickness of the benchmark is greater than the thickness of the test piece.

[0071] In some embodiments, the reference sheet is tightly bonded to the surface of the titanium-containing primer nanofilm layer away from the metal substrate by an insulating adhesive.

[0072] In some embodiments, the adhesive includes conventional non-conductive adhesive materials such as glue or instant adhesive.

[0073] refer to Figure 2 The specific steps of preparing the titanium-based nanofilm layer sample by using the method for preparing the titanium-based nanofilm layer sample of the present invention, that is, the specific steps of removing the metal substrate from the test piece by reaction, include:

[0074] Step S1: dissolving sulfuric acid and sulfate in deionized water to obtain a reaction solution.

[0075] The reaction solution is obtained by mixing sulfuric acid, sodium sulfate and deionized water and stirring to dissolve. The obtained reaction solution is placed in a reaction container such as Figure 3 The reaction container may be a reaction tank.

[0076] Among them, by adding a certain amount of sulfuric acid to the reaction solution, the pH value of the reaction solution is adjusted to less than 2 (i.e., the threshold value is the pH value less than 2), so as to prevent the metal ions dissolved from the substrate metal during the reaction from forming hydroxide precipitation, and from attaching and affecting the reaction, and causing pollution to the nanofilm layer. When the pH value of the reaction solution is less than 2, the substrate metal ions can be stably present in the solution in the form of ions.

[0077] By adding a certain amount of sulfate into the reaction solution, the reaction solution is made conductive.

[0078] In some embodiments, the sulfate salt includes at least one of sodium sulfate, potassium sulfate, and ammonium sulfate.

[0079] In some embodiments, the sulfuric acid concentration in the reaction solution is set to a range of 1.5 to 20 g / L, the sulfate concentration is set to a range of 5 to 100 g / L, and the balance is deionized water.

[0080] More preferably, the concentration of sulfuric acid in the reaction solution is set in the range of 2 to 12 g / L.

[0081] In some embodiments, the initial concentration of sulfuric acid in the reaction solution is 1.5 g / L, 1.6 g / L, 1.7 g / L, 1.8 g / L, 1.9 g / L, 2.0 g / L, 2.1 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L, 2.5 g / L, 2.6 g / L, 2.7 g / L, 2.8 g / L, 2.9 g / L, 3.0 g / L, 3.1 g / L, 3.2 g / L, 3.3 g / L, 3.4 g / L, 3.5 g / L, 3.6 g / L, 3.7 g / L, 3.8 g / L L, 3.9g / L, 4.0g / L, 4.1g / L, 4.2g / L, 4.3g / L, 4.4g / L, 4.5g / L, 4.6g / L, 4.7g / L, 4.8g / L, 4.9g / L, 5.0g / L, 5.1g / L, 5 .2g / L, 5.3g / L, 5.4g / L, 5.5g / L, 5.6g / L, 5.7g / L, 5.8g / L, 5.9g / L, 6.0g / L, 6.1g / L, 6.2g / L, 6.3g / L, 6.4g / L, 6.5g / L, 6.6g / L, 6.7g / L, 6.8g / L, 6.9g / L, 7.0g / L, 7.1g / L, 7.2g / L, 7.3g / L, 7.4g / L, 7.5g / L, 7.6g / L, 7.7g / L, 7.8g / L, 7 .9g / L, 8.0g / L, 8.1g / L, 8.2g / L, 8.3g / L, 8.4g / L, 8.5g / L, 8.6g / L, 8.7g / L, 8.8g / L, 8.9g / L, 9.0g / L, 9.1g / L, 9.2g / L, 9.3g / L, 9.4g / L, 9.5g / L, 9.6g / L, 9.7g / L, 9.8g / L, 9.9g / L, 10.0g / L, 10.1g / L, 10.5g / L, 11.0g / L, 12.0g / L, 13.0g / L, 14.0g / L, 15.0g / L, 16.0g / L, 17.0g / L, 18.0g / L, 19.0g / L, and 20.0g / L, or a concentration range of continuous variation with any two of the above concentrations as endpoints. In addition, during actual preparation, the initial preparation concentration of sulfuric acid can be fine-tuned up and down in units of 0.01g / L based on any of the above concentration values, or an up and down fluctuation of 0.05g / L is allowed to occur based on any of the above concentration values.

[0082] More preferably, the sulfate concentration in the reaction solution is set in the range of 16 to 80 g / L.

[0083] In this embodiment, the sulfate is sodium sulfate. Further, the initial concentration of sodium sulfate (sulfate) in the reaction solution is 5.0 g / L, 6.0 g / L, 7.0 g / L, 7.6 g / L, 7.8 g / L, 8.0 g / L, 8.1 g / L, 9.0 g / L, 10.0 g / L, 11.0 g / L, 12.0 g / L, 13.0 g / L, 14.0 g / L, 15.0 g / L, 15.1 g / L, 15.2 g / L, 16.0 g / L, 17.0 g / L, 18.0 g / L, 19.0 g / L, 20.0 g / L, 21.0 g / L, 22.0 g / L, 22.5 g / L, Any one of the concentrations of 23.0 g / L, 24.0 g / L, 25.0 g / L, 26.0 g / L, 27.0 g / L, 28.0 g / L, 29.0 g / L, 29.5 g / L, 29.8 g / L, 30.0 g / L, 30.1 g / L, 30.5 g / L, 35.0 g / L, 40.0 g / L, 45.0 g / L, 50.0 g / L, 52.5 g / L, 60.0 g / L, 70.0 g / L, 80.0 g / L, 90.0 g / L, and 100.0 g / L, or a continuously changing concentration range with any two of the above concentrations as endpoints. Furthermore, during actual preparation, the initial preparation concentration of sodium sulfate can be fine-tuned up or down by 0.01 g / L based on any of the above concentration values, or can be allowed to fluctuate up or down by 0.05 g / L based on any of the above concentration values.

[0084] Step S2: A test piece is prepared by using a metal substrate having a titanium-containing primer nanofilm layer plated on the surface, and an insulating reference sheet is bonded on the surface of the titanium-containing primer nanofilm layer.

[0085] For example, a metal substrate coated with a titanium-containing nanofilm layer is cut to form a rectangular specimen (reference Figure 4 (a)). But not limited to rectangular shapes.

[0086] Then, an insulating reference sheet is bonded to the top surface of the titanium-containing primer nanofilm layer. Taking a plastic sheet as a reference sheet as an example, a plastic sheet with the same length and width as the rectangular specimen is selected as the reference sheet. When bonding, the adhesive is first evenly applied to the surface of the titanium-containing primer nanofilm layer. Then, the reference sheet is gently placed on the surface of the titanium-containing primer nanofilm layer coated with the adhesive, and the plastic sheet is bonded to the sample and then used.

[0087] Adhesives are used to bond the test piece to the plastic sheet. On the one hand, the flat surface of the plastic sheet (reference sheet) is used as the reference plane for the titanium-containing base nano-film layer obtained later, ensuring the original state of the titanium-containing base nano-film layer structure on the prepared sample. On the other hand, a plastic sheet with a certain thickness is used to bond the nano-film layer on the test piece, so that the nano-film layer is firmly attached to the plastic sheet, forming an effective support for the titanium-containing base nano-film layer obtained later, and preventing the titanium-containing base nano-film layer from being damaged after the reaction is completed, which affects observation and testing. In addition, the bonded reference sheet can also be used to well protect the nano-film layer during the reaction, so that the nano-film layer immersed in the reaction solution will not be broken by the impact of bubbles generated by the reaction. Among them, the plastic sheet and the adhesive are non-conductive materials and will not participate in the reaction, so they can play an effective role in protecting the nanofilm layer during the separation process of the metal substrate and the titanium-containing primer nanofilm layer. After the reaction is completed, the retained nanofilm layer can be effectively fixed for a long time, and it is beneficial to directly observe the surface of the underlying primer layer of the titanium-containing primer nanofilm layer, and it is beneficial to prevent the nanofilm layer from being damaged secondary when further preparing slice samples through the sample.

[0088] In the process of bonding the plastic sheet to the test piece, the self-weight of the plastic sheet can be used to achieve a better fit between the plastic sheet and the test piece, so that the plastic sheet and the test piece are tightly bonded.

[0089] After the plastic sheet and the specimen are firmly bonded, the specimen can be placed in the reaction solution.

[0090] Step S3: The metal substrate on the specimen is used as an anode and the platinum electrode is used as a cathode, which are placed in a reaction solution, and a voltage is applied between the anode and the cathode to cause the metal substrate to react with the reaction solution and be dissolved and removed from the specimen.

[0091] Since the substrate metal is highly active such as iron and chromium, the titanium-containing base layer in the titanium-containing base nanofilm layer is a titanium base layer or a titanium alloy (the titanium content is greater than 30%, and does not contain other active metals) base layer. According to the metal standard electrode potential (see Table 1 below), when reacting in the reaction solution, active metals such as iron and chromium as the substrate metal will react before titanium. Therefore, the method of the present invention can be realized.

[0092] Table 1:

[0093] Electrode Process <![CDATA[E θ / V]]> <![CDATA[Fe 3+ +3e=Fe]]> -0.037 <h2 style=";text-align:left;direction:ltr"><![CDATA[Fe <h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> +2e = Fe<h2 style=";text-align:left;direction:ltr"> -0.447 <![CDATA[Cr 3+ +3e-=Cr]]> -0.744 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> +2e-=Ti]]><h2 style=";text-align:left;direction:ltr"> -1.63

[0094] refer to Figure 3 The metal substrate on the test piece bonded with the plastic sheet (reference sheet) was used as an anode and connected to a DC positive electrode (+), and the platinum electrode was used as a cathode and connected to a DC negative electrode (-).

[0095] Then, the coated specimen and the platinum electrode are placed in the reaction solution. After the power is turned on, the DC power supply will apply a certain voltage between the anode (metal substrate) and the cathode (platinum electrode), causing the substrate metal on the specimen to react and be gradually dissolved in the reaction solution, thereby achieving the automatic separation of the titanium-containing base nanofilm layer and the metal substrate.

[0096] It is worth noting that the voltage applied by the DC power supply between the anode and the cathode should be smaller than the voltage required for the titanium-containing primer material in the titanium-containing primer nanofilm layer to react with the reaction solution.

[0097] In some embodiments, when a voltage is applied between the anode and the cathode, the method specifically includes: first setting the range of voltage that can be applied. During the entire reaction stage, a voltage is applied between the anode and the cathode in a manner that the voltage value gradually decreases within the set voltage range, so that the reaction rate of the metal substrate when reacting with the reaction liquid changes from high to low. In this way, in the initial stage of the reaction, a higher voltage can be applied to accelerate the reaction rate of the metal substrate so that it can be dissolved at a faster rate, and as the reaction proceeds, the voltage is gradually reduced to adapt to the thinning thickness and smaller area of ​​the metal substrate, so as to prevent the impact effect of the high voltage on the titanium-containing primer material gradually exposed behind the metal substrate and cause damage to the titanium-containing primer layer. In addition, compared with the method of applying a constant voltage, the reaction time can also be shortened.

[0098] In some embodiments, when a voltage is applied between the anode and the cathode, the method specifically includes: first setting the range of voltage that can be applied. In the entire reaction stage, a voltage is applied between the anode and the cathode in a manner that the voltage value is gradually increased and then gradually decreased within the set voltage range, so that the reaction rate when the metal substrate reacts with the reaction solution changes from low to high and then to low. In this way, in the initial stage of the reaction, by first applying a lower voltage, it is possible to avoid the impact effect on the exposed edge of the titanium-containing primer layer caused by the excessively high initial voltage, thereby causing damage to the titanium-containing primer layer. Then, the voltage is gradually increased to gradually accelerate the reaction rate of the metal substrate, and it can be observed to determine whether the maximum value of the applied voltage is appropriate to avoid excessive voltage. When the thickness of the metal substrate is already very thin, or the area becomes smaller and the titanium primer layer is exposed, the voltage is gradually reduced to prevent the impact effect on the titanium-containing primer material gradually exposed behind the metal substrate from causing damage to the titanium-containing primer layer. In addition, compared with the method of applying a constant voltage, the reaction time can also be shortened.

[0099] In some embodiments, the pH value and sulfate concentration of the reaction solution are analyzed during the entire reaction stage. When the analyzed pH value exceeds a threshold value (less than 2), sulfuric acid is added to the reaction solution according to a set sulfuric acid concentration range so that the pH value falls back within the threshold value to prevent the metal ions dissolved from the substrate metal during the reaction from forming hydroxide precipitation and attaching to affect the reaction.

[0100] When the analyzed sulfate concentration exceeds the lower limit of the set sulfate concentration range, sulfate is added to the reaction solution to make the sulfate concentration reach the median of the set sulfate concentration range or the initial preparation concentration of sulfate to ensure the normal progress of the reaction.

[0101] In some embodiments, the voltage range of the DC power supply applied between the anode and the cathode is set to be 2 to 7 V, and the current density range applied to the anode (metal substrate) is set to be 150 to 700 A / m 2 .

[0102] In some embodiments, the substrate metal includes iron (steel).

[0103] In some embodiments, the base layer material in the titanium-containing base nanofilm layer includes pure titanium, CNTi or TiN.

[0104] In some embodiments, the voltage setting value applied by the DC power supply between the anode (iron) and the cathode is specifically 2.0V, 2.1V, 2.2V, 2.3V, 2.4V, 2.5V, 2.6V, 2.7V, 2.8V, 2.9V, 3.0V, 3.1V, 3.2V, 3.3V, 3.4V, 3.5V, 3.6V, 3.7V, 3.8V, 3.9V, 4.0V, 4.1V, 4.2V, 4.3V, 4.4V, 4.5V, 4.6V, 4.7V, 4.8V, 4.9V, 5.0V, 5.1V, 5.2V, 5.3V, 5.4V, 5.5V, 5.6V, 5.7V, 5.8V, 5.9V, 6.0V, 6.1V, 6.2V, 6.3V, 6.4V, 6.5V, 6.6V, 6.7V, 6.8V, 6.9V, 7.0V, 7.1V, 7.2V, 7.3V, 7.4V, 7.5V, 7.6V, 7.7V, 7.8V, 7.9V, 8.0V, 8.1V, 8.2V, 8.3V, 8.4V, 8.5V, 8 ... Any one of the voltage values ​​​​among 4.6V, 4.7V, 4.8V, 4.9V, 5.0V, 5.1V, 5.2V, 5.3V, 5.4V, 5.5V, 5.6V, 5.7V, 5.8V, 5.9V, 6.0V, 6.1V, 6.2V, 6.3V, 6.4V, 6.5V, 6.6V, 6.7V, 6.8V, 6.9V, 7.0V, or a continuously changing voltage value range with any two of the above voltage values ​​as endpoints. In addition, when actually setting, it is possible to make a fine adjustment up and down in units of 0.01V based on any of the above voltage values, or allow an up and down fluctuation of 0.05V based on any of the above voltage values.

[0105] In some embodiments, the current density applied to the anode (iron) is 150 A / m 2 , 155A / m 2 , 160A / m 2 , 165A / m2 , 170A / m 2 , 175A / m 2 , 180A / m 2 , 185A / m 2 , 190A / m 2 , 195A / m 2 , 200A / m 2 , 250A / m 2 , 300A / m 2 , 350A / m 2 , 400A / m 2 , 450A / m 2 , 455A / m 2 , 460A / m 2 , 465A / m 2 , 470A / m 2 , 480A / m 2 , 490A / m 2 , 500A / m 2 , 525A / m 2 , 550A / m 2 , 600A / m 2 , 640A / m 2 , 650A / m 2 , 660A / m 2 , 668A / m 2 , 670A / m 2 , 680A / m 2 , 690A / m 2 , 700A / m 2 Any current density value in , or a continuously changing current density value range with any two of the above current density values ​​as endpoints.

[0106] Moreover, during the reaction process, the current density can change accordingly with the change of voltage.

[0107] It is worth noting that, since the voltage applied by the DC power supply between the anode and the cathode is relatively low, the reaction conditions of the titanium base material in the titanium base nanofilm layer are not achieved. Thus, during the reaction process, within the voltage range, only the base metal iron will form iron ions, but the titanium of the base material will not form titanium ions, so even if the reaction time is too long, it will not affect the separation of the film layer, thus fully ensuring the stability of the film separation process and the repeatability of the method, and ensuring the integrity and availability of the separated nanofilm.

[0108] Step S4: taking out the reacted test piece from the reaction solution, immersing and cleaning it in pure water, and air-drying the cleaned test piece.

[0109] Through visual observation (it can be judged by color that the substrate surface is generally rough, while the exposed titanium-containing bottom layer of the nano-film layer has a bright mirror-like metallic luster), when the metal substrate is completely dissolved or dissolved to the target position that meets the area requirements of subsequent tests, the power is cut off to complete the reaction process.

[0110] At this time, the treated specimen is taken out of the reaction solution and removed from the electrode. Then, the specimen is soaked in pure water for cleaning to remove the residual reaction solution on the specimen to avoid crystallization during the subsequent drying process, which may affect subsequent testing. The soaking time is 5 to 15 minutes, preferably about 10 minutes.

[0111] Finally, the test piece is air-dried to obtain the target film layer (titanium-containing primer nano-film layer) bonded to the plastic sheet, thereby obtaining a titanium-containing primer nano-film layer sample.

[0112] The titanium-containing primer nanofilm layer sample prepared by the above-mentioned titanium-containing primer nanofilm layer sample preparation method of the present invention comprises a titanium-containing primer nanofilm layer whose surface is bonded to the surface of an insulating reference sheet by an insulating adhesive, and whose metal substrate originally serving as a base is removed by reaction. The titanium-containing primer nanofilm layer sample can not only be used to directly observe and test the surface of the titanium-containing primer nanofilm layer retained on the reference sheet after the reaction (the surface originally in contact with the metal substrate), but can also be used to further prepare slice samples.

[0113] Embodiment 1

[0114] The method for preparing a titanium-containing primer nanofilm layer sample of the present invention is implemented according to the following steps:

[0115] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 7 g / L and a sodium sulfate concentration of 15 g / L.

[0116] 2. Cover the film surface of the specimen 1 to be treated (using a 316 stainless steel substrate with a size of 2×4 cm and a thickness of 0.2 mm (the same below), coated with a nanofilm layer having a film structure of a single Ti layer (titanium base layer)) with a non-conductive adhesive, and bond it tightly to the specimen 1 with a plastic sheet.

[0117] 3. The 316 stainless steel substrate of the above-mentioned specimen 1 is connected to the positive electrode of direct current, and the platinum electrode is connected to the negative electrode of direct current, and placed in the above-mentioned reaction solution, so that the 316 stainless steel substrate on the specimen 1 is corroded by the reaction, leaving a titanium-based nanofilm layer on the plastic sheet.

[0118] 4. Turn on the power supply so that the DC power supply applies a maximum voltage of 4V between the two electrodes and a maximum current density of 450A / m 2The reaction temperature is room temperature. The voltage is gradually applied by gradually increasing the voltage from 2V to 4V and then gradually decreasing the voltage from 4V to 3V.

[0119] 5. Visually observe the reaction until the 316 stainless steel substrate is completely dissolved, and then cut off the power supply. The reaction takes about 37 hours.

[0120] 6. Remove the reacted specimen 1 from the electrode, soak it in pure water for cleaning, remove the residual reaction liquid, and then dry the specimen 1 to obtain the target film layer.

[0121] The morphology of the 316 stainless steel substrate on the specimen 1 before reaction (separation) is as follows Figure 4 As shown in (a), the 316 stainless steel substrate on the specimen 1 after reaction (separation) has been removed, and the morphology of the target film layer obtained (the silver film layer on the surface is the titanium base layer as the nano film layer) is shown in Figure 4 (b) As shown. It can be seen that the film area integrity of the titanium-containing base nanofilm after the reaction exceeds 90%. By comparing the film thickness of the film structure after separation with that of the film structure of the sliced ​​sample prepared using the specimen 1 before separation, Figure 5 The measured film thickness of the film structure of the sliced ​​sample in (a) (before separation) is 709.2nm (the distance marked by the vertical red line in the figure, the same below). Figure 5 The film thickness of the titanium-containing nanofilm layer separated by the above method in (b) is 709.2nm. The film thickness measurements of the two are consistent, and the film layers before and after separation are the same ( Figure 5 The film layer at No.1 in (a) is Figure 5 (b) corresponds to the film layer at No. 2 marked).

[0122] Embodiment 2

[0123] The method for preparing a titanium-containing primer nanofilm layer sample of the present invention is implemented according to the following steps:

[0124] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 2 g / L and a sodium sulfate concentration of 8 g / L.

[0125] 2. Cover the film surface of the specimen 2 to be treated (316 stainless steel substrate, nano-film layer with a total of 6 film layers, namely CNTi layer (containing titanium base layer), CTi layer, CuOFe layer, COTi layer, COTi layer, and CNOTi layer) with a non-conductive adhesive, and bond it tightly to the specimen 2 with a plastic sheet.

[0126] 3. The 316 stainless steel substrate of the above-mentioned specimen 2 is connected to the positive electrode of direct current, and the platinum electrode is connected to the negative electrode of direct current, and placed in the above-mentioned reaction solution, so that the 316 stainless steel substrate on the specimen 2 is corroded by the reaction, leaving a titanium-based nanofilm layer on the plastic sheet.

[0127] 4. Turn on the power supply so that the DC power supply applies a constant voltage of 6V between the two electrodes and the current density is 190A / m 2 , the reaction temperature is room temperature.

[0128] 5. Visually observe the reaction until the 316 stainless steel substrate is completely dissolved, and then cut off the power supply. The reaction takes about 48 hours.

[0129] 6. Remove the reacted specimen 2 from the electrode, soak it in pure water for cleaning, remove the residual reaction liquid, and then dry the specimen 2 to obtain the target film layer.

[0130] The morphology of the 316 stainless steel substrate on specimen 2 before reaction (separation) is as follows: Figure 6 As shown in (a), the 316 stainless steel substrate on the specimen 2 after reaction (separation) has been removed, and the morphology of the target film layer obtained (the silver film layer on the surface is the titanium-containing primer layer located at the bottom of the nanofilm layer) is shown in Figure 6 (b) As shown. It can be seen that the film area integrity of the titanium-containing base nanofilm after the reaction exceeds 90%. By comparing the film thickness of the film structure after separation with that of the film structure of the sliced ​​sample prepared using the sample 2 before separation, Figure 7 The total film thickness of the film structure of the sliced ​​sample in (a) (before separation) is measured to be 1.68 μm. Figure 7 The total film thickness of the titanium-containing bottom nanofilm layer separated by the above method in (b) is 1.62 μm. The film thickness measurements of the two are relatively consistent, and the film layers before and after separation are the same (the titanium-containing bottom nanofilm layer includes 6 film layers, Figure 7 The film layers at No.1, No.2, No.3, No.4, No.5, No.6, and No.7 marked in (a) are Figure 7 The film layers marked at No.7, No.1, No.2, No.3, No.4, No.5 and No.6 in (b) correspond respectively).

[0131] Embodiment 3

[0132] The method for preparing a titanium-containing primer nanofilm layer sample of the present invention is implemented according to the following steps:

[0133] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 10 g / L and a sodium sulfate concentration of 30 g / L.

[0134] 2. Cover the film surface of the specimen 3 to be treated (316 stainless steel substrate, nano-film layer with a total of 6 film layers, namely CNTi layer (containing titanium base layer), CTi layer, CuOFe layer, COTi layer, COTi layer, and CNOTi layer) with a non-conductive adhesive, and bond it tightly to the specimen 3 with a plastic sheet.

[0135] 3. The 316 stainless steel substrate of the above-mentioned specimen 3 is connected to the positive electrode of direct current, and the platinum electrode is connected to the negative electrode of direct current, and placed in the above-mentioned reaction solution, so that the 316 stainless steel substrate on the specimen 3 is corroded by the reaction, leaving a titanium-based nanofilm layer on the plastic sheet.

[0136] 4. Turn on the power supply so that the DC power supply applies a maximum voltage of 6V between the two electrodes and a maximum current density of 670A / m 2 The reaction temperature is room temperature. The voltage is gradually applied by gradually decreasing the voltage from 6V to 4.5V.

[0137] 5. Visually observe the reaction until the 316 stainless steel substrate is completely dissolved, and then cut off the power supply. The reaction takes about 34 hours.

[0138] 6. Remove the reacted specimen 3 from the electrode, soak and clean it in pure water to remove the residual reaction solution, and then dry the specimen 3 to obtain the target film layer.

[0139] The morphology of the 316 stainless steel substrate on the specimen 3 before reaction (separation) is as follows: Figure 8 As shown in (a), the 316 stainless steel substrate on the specimen 3 after reaction (separation) has been removed, and the morphology of the target film layer obtained (the silver film layer on the surface is the titanium-containing primer layer located at the bottom of the nanofilm layer) is shown in Figure 8 (b) As shown. It can be seen that the film area integrity of the titanium-containing base nanofilm layer after the reaction exceeds 90%. By comparing the film thickness of the film structure after separation with that of the film structure of the sliced ​​sample prepared using the sample 3 before separation, Fig. 9 The total film thickness of the film structure of the sliced ​​sample in (a) (before separation) is measured to be 1.680 μm. Fig. 9 The total film thickness of the titanium-containing nanofilm layer separated by the above method in (b) is 1.665 μm. The film thickness measurements of the two are relatively consistent, and the film layers before and after separation are the same (the titanium-containing nanofilm layer includes 6 film layers, Fig. 9 The film layers at No.1, No.2, No.3, No.4, No.5, No.6, and No.7 marked in (a) are Fig. 9 The film layers marked No. 1, No. 2, No. 3, No. 4, No. 5, No. 6, and No. 7 in (b) correspond respectively).

[0140] Embodiment 4

[0141] The method for preparing a titanium-containing primer nanofilm layer sample of the present invention is implemented according to the following steps:

[0142] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 10 g / L and a sodium sulfate concentration of 60 g / L.

[0143] 2. Cover the film surface of the specimen 4 to be treated (316 stainless steel substrate, nano-film layer with a two-layer film structure of Ti layer (titanium base layer) and TAC layer in sequence) with a non-conductive adhesive, and bond it tightly to the specimen 4 with a plastic sheet.

[0144] 3. The 316 stainless steel substrate of the above-mentioned specimen 4 is connected to the positive electrode of direct current, and the platinum electrode is connected to the negative electrode of direct current, and placed in the above-mentioned reaction solution, so that the 316 stainless steel substrate on the specimen 4 is corroded by the reaction, leaving a titanium-based nanofilm layer on the plastic sheet.

[0145] 4. Turn on the power supply so that the DC power supply applies a voltage of 3.2V between the two electrodes and a current density of 350A / m 2 , the reaction temperature is room temperature.

[0146] 5. Visually observe the reaction until the 316 stainless steel substrate has dissolved to the point where the surface of the nanofilm layer is effectively exposed (the figure shows that the nanofilm layer is basically half exposed), then cut off the power supply. The reaction takes about 32 hours.

[0147] 6. Remove the reacted specimen 4 from the electrode, soak it in pure water for cleaning, remove the residual reaction liquid, and then dry the specimen 4 to obtain the target film layer.

[0148] The morphology of the 316 stainless steel substrate on the specimen 4 before reaction (separation) is as follows Fig.10 As shown in (a), the 316 stainless steel substrate on the specimen 4 after reaction (separation) has been partially removed, and the morphology of the target film layer obtained is as follows: Fig.10 (b) Fig.10 (b) The film morphology shown in the upper part of the figure). It can be seen that the film area integrity of the titanium-containing base nanofilm layer exposed after the reaction exceeds 90%. By comparing the film thickness of the film structure after separation with that of the film structure of the sliced ​​sample prepared using the sample 4 before separation, Fig.11 The total film thickness of the film structure of the sliced ​​sample in (a) (before separation) is measured to be 1.224 μm. Fig.11 The total film thickness of the titanium-containing bottoming nanofilm layer separated by the above method in (b) is 1.172 μm. The film thickness measurements of the two are relatively consistent, and the film layers before and after separation are the same (the titanium-containing bottoming nanofilm layer includes 2 film layers, Fig.11The film layers at No.1, No.2, and No.3 in (a) are Fig.11 The film layers at No.2, No.3, and No.1 marked in (b) correspond respectively).

[0149] Embodiment 5

[0150] The method for preparing a titanium-containing primer nanofilm layer sample of the present invention is implemented according to the following steps:

[0151] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 10 g / L and a sodium sulfate concentration of 90 g / L.

[0152] 2. Cover the film surface of the specimen 5 to be treated (316 stainless steel substrate, nano-film layer with a single-layer film structure of TiN layer (containing titanium base layer)) with a non-conductive adhesive, and adhere the specimen 5 closely with a plastic sheet.

[0153] 3. The 316 stainless steel substrate of the above-mentioned specimen 5 is connected to the positive electrode of direct current, and the platinum electrode is connected to the negative electrode of direct current, and placed in the above-mentioned reaction solution, so that the 316 stainless steel substrate on the specimen 5 is corroded by the reaction, leaving a nano-film layer containing titanium as the base on the plastic sheet.

[0154] 4. Turn on the power supply so that the DC power supply applies a voltage of 2.9V between the two electrodes and a current density of 450A / m 2 , the reaction temperature is room temperature.

[0155] 5. Visually observe the reaction until the 316 stainless steel substrate has dissolved to the point where the surface of the nanofilm layer is effectively exposed (the figure shows that most of the nanofilm layer is exposed), then cut off the power supply. The reaction takes about 48 hours.

[0156] 6. Remove the reacted specimen 5 from the electrode, soak it in pure water for cleaning, remove the residual reaction solution, and then dry the specimen 5 to obtain the target film layer.

[0157] The morphology of the 316 stainless steel substrate on the specimen 5 before reaction (separation) is as follows: Fig.12 As shown in (a), the 316 stainless steel substrate on the specimen 5 after reaction (separation) has been mostly removed, and the morphology of the target film layer obtained is as follows: Fig.12 (b) Fig.12 (b) The right part of the figure shows the film morphology). It can be seen that the film area integrity of the titanium-containing base nanofilm layer exposed after the reaction exceeds 75%. By comparing the film thickness of the film structure after separation with that of the film structure of the sliced ​​sample prepared using the sample 5 before separation, Fig.13The total film thickness of the film structure of the sliced ​​sample in (a) (before separation) is measured to be 3.324 μm (due to the influence of resin coverage, the test result is smaller). Fig.13 The total film thickness of the titanium-containing base nanofilm layer separated by the above method in (b) is measured to be 3.424 μm. The film thickness measurement values ​​of the two are relatively consistent, and the film layers are the same before and after separation.

[0158] Embodiment 6

[0159] The method for preparing a titanium-containing primer nanofilm layer sample of the present invention is implemented according to the following steps:

[0160] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 15 g / L and a sodium sulfate concentration of 80 g / L.

[0161] 2. Cover the film surface of the specimen 6 to be treated (316 stainless steel substrate, nano-film layer with a single-layer film structure of TiN layer (containing titanium base layer)) with a non-conductive adhesive, and adhere the specimen 6 closely with a plastic sheet.

[0162] 3. The 316 stainless steel substrate of the above-mentioned specimen 6 is connected to the positive electrode of direct current, and the platinum electrode is connected to the negative electrode of direct current, and placed in the above-mentioned reaction solution, so that the 316 stainless steel substrate on the specimen 6 is corroded by the reaction, leaving a titanium-based nanofilm layer on the plastic sheet.

[0163] 4. Turn on the power supply so that the DC power supply applies a voltage of 2.9V between the two electrodes and a current density of 420A / m 2 , the reaction temperature is room temperature.

[0164] 5. Visually observe the reaction until the 316 stainless steel substrate dissolves and the nanofilm layer is exposed, then cut off the power supply. The reaction of specimen 6 takes about 48 hours to complete.

[0165] 6. Remove the reacted specimen 6 from the electrode, soak it in pure water for cleaning, remove the residual reaction liquid, and then dry the specimen 6 to obtain the target film layer.

[0166] The morphology of the 316 stainless steel substrate on the specimen 6 before reaction (separation) is as follows Fig.14 As shown in (a), the morphology of the sample 6 after reaction (separation) is as follows Fig.14 (b) As shown. It can be seen that the film area integrity of the titanium-containing primer nanofilm layer exposed after the reaction is less than 40% ( Fig.14 (b) The bright part shows that part of the metal substrate has not been dissolved during the reaction, and some of the film layer has been dissolved by reaction, but it can still be used for film layer testing. By comparing the film layer thickness of the residual film layer structure after separation with the film layer structure of the sliced ​​sample prepared using the specimen 6 before separation, Fig.15The total film thickness of the film structure of the sliced ​​sample in (a) (before separation) is measured to be 247.1 nm. Fig.15 The total film thickness of the titanium-containing primer nanofilm layer separated by the above method in (b) is 238.9 nm. The film thickness measurements of both are within the test error, and the film layers before and after separation are the same. In this example, because the concentrations of sulfuric acid and sodium sulfate used are both high, the experimental results are affected to a certain extent, and the film area integrity is less than the film area integrity obtained in the above embodiment.

[0167] Embodiment 7

[0168] The method for preparing a titanium-containing primer nanofilm layer sample of the present invention is implemented according to the following steps:

[0169] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 7 g / L and a sodium sulfate concentration of 40 g / L.

[0170] 2. Cover the film surface of the specimen 7 to be processed (316 stainless steel substrate, nano-film layer with a single-layer film structure of TiN layer (containing titanium base layer)) with a non-conductive adhesive, and adhere the specimen 7 closely with a plastic sheet.

[0171] 3. The 316 stainless steel substrate of the above-mentioned specimen 7 is connected to the positive electrode of direct current, and the platinum electrode is connected to the negative electrode of direct current, and placed in the above-mentioned reaction solution, so that the 316 stainless steel substrate on the specimen 7 is corroded by the reaction, leaving a titanium-based nanofilm layer on the plastic sheet.

[0172] 4. Turn on the power supply so that the DC power supply applies a voltage of 8V between the two electrodes and a current density of 1000A / m 2 , the reaction temperature is room temperature.

[0173] 5. Visually observe the reaction until the 316 stainless steel substrate dissolves and the nanofilm layer is exposed, then cut off the power supply. The reaction of specimen 7 takes about 12 hours to complete.

[0174] 6. Remove the reacted specimen 7 from the electrode, soak it in pure water for cleaning, remove the residual reaction liquid, and then dry the specimen 7.

[0175] The morphology of the 316 stainless steel substrate on the specimen 7 before reaction (separation) is as follows: Fig.16 As shown in (a), the morphology of the sample 7 after reaction (separation) is as follows Fig.16 (b) As shown. It can be seen that the film area integrity of the titanium-containing bottom nanofilm layer exposed after the reaction is less than 10% ( Fig.16The upper left part in (b) is the remaining metal substrate, and the shiny part on the right and below the metal substrate is the film layer). The film layer was broken during the reaction. The film thickness of the film layer structure of the residual film layer after separation was compared with that of the film layer structure of the sliced ​​sample prepared using the specimen 7 before separation. Fig.17 The total film thickness of the film structure of the sliced ​​sample in (a) (before separation) is measured to be 247.1 nm. Fig.17 The total film thickness of the titanium-containing primer nanofilm layer separated by the above method in (b) is 283.7nm, and the film thickness measurement values ​​of both are still within the test error, and the film layers before and after separation are the same. In this example, because the voltage and current density used exceed the upper limit of the voltage range and the upper limit of the current density range, the film area integrity of the titanium-containing primer nanofilm layer obtained after the reaction is very small.

[0176] It can be seen from the above-mentioned Examples 1 to 6 that the desired titanium-based nanofilm layer can be obtained well after the reaction by conducting experiments under different concentrations, voltages and current densities of the reaction solution within the set range. The exposed surface of the titanium-based nanofilm layer can be used for abnormal observation and testing, and can also meet the needs of further sample preparation. In particular, even if the reaction time is extended, no obvious damage will be caused to the titanium-based nanofilm layer.

[0177] It should be noted that the local undulating morphology of the surface of the titanium-based nanofilm layer after the reaction in the above figures has little effect on the analysis of the film structure, because the magnitude of the film structure is basically at the nanometer scale. If abnormal particles appear at the bottom of the film, they can also be found, regardless of whether the film surface is undulating.

[0178] Comparative Example 1

[0179] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 5 g / L and a sodium sulfate concentration of 15 g / L.

[0180] 2. The 316 stainless steel substrate of the test piece 8 to be treated (316 stainless steel substrate, nano-film layer with a total of 6 film layers, namely CNTi layer (containing titanium base layer), CTi layer, CuOFe layer, COTi layer, COTi layer, and CNOTi layer) that has not been bonded to the plastic sheet is directly connected to the positive electrode of direct current, and the platinum electrode is connected to the negative electrode of direct current, and placed in the above-mentioned reaction solution.

[0181] 3. Turn on the power supply so that the DC power supply applies a voltage of 7V between the two electrodes and a current density of 680A / m 2 , the reaction temperature is room temperature.

[0182] 4. Visually observe the reaction until the 316 stainless steel substrate is completely dissolved.

[0183] 5. Remove the remaining test piece 8 from the electrode after the reaction, soak and clean it in pure water to remove the remaining reaction liquid, and then dry the test piece 8.

[0184] The morphology of the 316 stainless steel substrate on the specimen 8 before reaction (separation) is as follows: Fig.18 (a). Fig.18 As shown in (b), it can be seen that the 316 stainless steel substrate portion of the test piece 8 located in the reaction liquid after the reaction (separation) has been largely dissolved (the left part is the remaining material after the reaction (the dark part), and the 316 stainless steel substrate portion with holes on the right (the bright part) is located outside the reaction liquid and is therefore not corroded). However, since the test piece 8 was not bonded to the plastic sheet, the titanium-containing primer nanofilm layer on the 316 stainless steel substrate was directly in contact with the reaction liquid and was broken during the reaction due to the corrosion and dissolution of the 316 stainless steel substrate. Although there may still be a film layer on the remaining material after the reaction on the left side of the figure, it can no longer be collected.

[0185] Comparative Example 2

[0186] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 1 g / L and a sodium sulfate concentration of 120 g / L.

[0187] 2. Cover the film surface of the specimen 9 to be treated (316 stainless steel substrate, nano-film layer with a two-layer film structure of Cr layer (Cr base layer) and CrC layer in sequence) with a non-conductive adhesive, and bond it tightly to the specimen 9 with a plastic sheet.

[0188] 3. Connect the 316 stainless steel substrate of the above-mentioned test piece 9 to the positive electrode of direct current, connect the platinum electrode to the negative electrode of direct current, and place them in the above-mentioned reaction solution.

[0189] 4. Turn on the power supply so that the DC power supply applies a voltage of 5.4V between the two electrodes and a current density of 800A / m 2 The reaction temperature is room temperature. The current density used in this comparative example is greater than the upper limit of the current density of the present invention, 700A / m 2 .

[0190] 5. Visually observe the reaction until the 316 stainless steel substrate is completely dissolved.

[0191] 6. Remove the reacted specimen 9 from the electrode, soak it in pure water to clean the remaining reaction liquid, and then dry the specimen 7.

[0192] The morphology of the 316 stainless steel substrate on the specimen 9 before reaction (separation) is as follows Fig.19 (a). Fig.19 As shown in (b), it can be seen that the sample 9 after reaction (separation) Fig.19(b) The 316 stainless steel substrate on the upper side of the figure has been basically dissolved, and only the left side (with holes) still has some 316 stainless steel substrate (white part) left after the reaction. However, because the nanofilm layer of specimen 9 uses highly active chromium as the base layer, under the above voltage and current density conditions, chromium corrodes and dissolves along with the corrosion and dissolution of the 316 stainless steel substrate during the reaction process, so that the nanofilm layer bonded with the plastic sheet is mostly broken and sinks in the reaction solution ( Fig.19 (b) The reaction liquid in the container shown in the figure below has been absorbed by the 316 stainless steel substrate, and only a small amount of film remains near the remaining 316 stainless steel substrate, but it is difficult to collect and utilize due to its small area.

[0193] Comparative Example 3

[0194] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 10 g / L and a sodium sulfate concentration of 30 g / L.

[0195] 2. Cover the film surface of the specimen 10 to be treated (316 stainless steel substrate, nano-film layer with a two-layer film structure of Cr layer (Cr base layer) and CrC layer in sequence) with a non-conductive adhesive, and bond the specimen 10 tightly with a plastic sheet.

[0196] 3. Connect the 316 stainless steel substrate of the above-mentioned test piece 10 to the positive electrode of direct current, connect the platinum electrode to the negative electrode of direct current, and place them in the above-mentioned reaction solution.

[0197] 4. Turn on the power supply so that the DC power supply applies a voltage of 3.1V between the two electrodes and a current density of 170A / m 2 , the reaction temperature is room temperature.

[0198] 5. Visually observe the reaction to see if the 316 stainless steel substrate is at least partially dissolved.

[0199] 6. Remove the test piece 10 from the electrode after the reaction, soak it in pure water to clean the remaining reaction liquid, and then dry the test piece 10.

[0200] The morphology of the 316 stainless steel substrate on the specimen 10 before reaction (separation) is as follows Fig. 20 (a). Fig. 20 As shown in (b), it can be seen that after the reaction (separation), only part of the 316 stainless steel substrate (white part) that has not been completely reacted still exists in the middle part of the test piece 10. However, because the nano-film layer of the test piece 10 uses chromium with high activity as the base layer, under the above voltage and current density conditions, the chromium corrodes and dissolves along with the corrosion and dissolution of the 316 stainless steel substrate during the reaction process, so that the nano-film layer bonded with the plastic sheet is basically dissolved, and only some carbon in the CrC film layer remains around the remaining 316 stainless steel substrate, and the other film layers no longer exist.

[0201] Comparative Example 4

[0202] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 10 g / L and a sodium sulfate concentration of 30 g / L.

[0203] 2. Cover the film surface of the specimen 11 to be treated (316 stainless steel substrate, nano-film layer with a film structure of 3 layers, namely, Cr layer (Cr base layer), CrC layer, and C layer) with a non-conductive adhesive, and bond the specimen 11 tightly with a plastic sheet.

[0204] 3. Connect the 316 stainless steel substrate of the above-mentioned test piece 11 to the positive electrode of direct current, connect the platinum electrode to the negative electrode of direct current, and place them in the above-mentioned reaction solution.

[0205] 4. Turn on the power supply so that the DC power supply applies a voltage of 3.5V between the two electrodes and a current density of 200A / m 2 , the reaction temperature is room temperature.

[0206] 5. Visually observe the reaction until the 316 stainless steel substrate is basically dissolved.

[0207] 6. Remove the reacted specimen 11 from the electrode, soak it in pure water to clean the remaining reaction solution, and then dry the specimen 11.

[0208] The morphology of the 316 stainless steel substrate on the specimen 11 before reaction (separation) is as follows Fig.21 (a). Fig.21 As shown in (b), it can be seen that the 316 stainless steel substrate on the test piece 11 after the reaction (separation) has been mostly dissolved (the part near the hole on the left is the 316 stainless steel substrate remaining after the reaction (white part)), but because the nano film layer of the test piece 11 uses the highly active chromium as the base layer, under the above voltage and current density conditions, the chromium corrodes and dissolves along with the corrosion and dissolution of the 316 stainless steel substrate during the reaction process, so that the nano film layer bonded with the plastic sheet is completely dissolved, and no film layer is left.

[0209] Comparative Example 5

[0210] 1. Mix sulfuric acid, sodium sulfate and deionized water, stir and dissolve, and prepare a reaction solution with a sulfuric acid concentration of 10 g / L and a sodium sulfate concentration of 50 g / L.

[0211] 2. Cover the film surface of the specimen 12 to be processed (316 stainless steel substrate, nano-film layer with a two-layer film structure of AlN layer (AlN base layer) and AlCrN layer in sequence) with a non-conductive adhesive, and bond the specimen 12 tightly with a plastic sheet.

[0212] 3. Connect the 316 stainless steel substrate of the above-mentioned test piece 12 to the positive electrode of direct current, connect the platinum electrode to the negative electrode of direct current, and place them in the above-mentioned reaction solution.

[0213] 4. Turn on the power supply so that the DC power supply applies a voltage of 3.5V between the two electrodes and a current density of 350A / m 2 , the reaction temperature is room temperature.

[0214] 5. Visually observe the reaction until the 316 stainless steel substrate is completely dissolved.

[0215] 6. Remove the reacted specimen 12 from the electrode, soak it in pure water to clean the remaining reaction solution, and then dry the specimen 12.

[0216] The morphology of the 316 stainless steel substrate on the specimen 12 before reaction (separation) is as follows Fig. 22 (a). Fig. 22 As shown in (b), it can be seen that the 316 stainless steel substrate on the test piece 12 after the reaction (separation) has been basically dissolved (the left part is the 316 stainless steel substrate part (white part) that is retained after the reaction because it has not contacted the reaction liquid, and the 316 stainless steel substrate part that has contacted the reaction liquid has been completely dissolved after the reaction). However, because the nano-film layer of the test piece 12 uses the highly active AlN as the base layer, under the above voltage and current density conditions, AlN corrodes and dissolves along with the corrosion and dissolution of the 316 stainless steel substrate during the reaction process, so that the nano-film layer bonded with the plastic sheet is completely dissolved, and no film layer is left.

[0217] It can be seen from the above comparative examples that when the surface of the nanofilm layer is not attached with a plastic sheet, even if the nanofilm layer is a titanium-based nanofilm layer, it cannot be obtained after the reaction test. When the nanofilm layer uses Cr, Al and other materials with higher activity than Ti as the base material, even if a plastic sheet is attached to the surface of the nanofilm layer, the nanofilm layer with the Cr or Al material base cannot be obtained after the reaction test.

[0218] In summary, the present invention firstly adheres the insulating reference sheet to the surface of the titanium-containing primer nanofilm layer on the test piece, and exposes the metal substrate, and then removes the metal substrate from the test piece through reaction, so as to obtain the titanium-containing primer nanofilm layer retained on the target area of ​​the reference sheet, which can be further used to study film defects and perform related performance tests, so as to achieve comprehensive and accurate observation and testing of abnormalities at the bottom of the film layer. At the same time, since there is no metal substrate on the sample sheet, when it is further used to prepare sliced ​​samples, it also effectively avoids the problem that the sample preparation fails due to the large difference in grinding rate between the metal substrate and the nanofilm material for some film materials with high brittleness due to the film breaking caused by grinding. The present invention is simple and easy to implement, low in cost, and suitable for application.

[0219] The above are only preferred embodiments of the present invention, and the embodiments are not intended to limit the protection scope of the present invention. Therefore, all equivalent changes made using the description and drawings of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a titanium-containing nanofilm layer sample, characterized in that: include: Providing a test piece, the test piece comprising a titanium-containing primer nanofilm layer plated on a surface of a metal substrate; The insulating reference sheet is closely attached to the surface of the titanium-containing primer nanofilm layer away from the metal substrate; The metal substrate is removed from the test piece by reaction, so that the titanium-containing primer nanofilm layer remains on the reference piece and the surface of the titanium-containing primer nanofilm layer close to the metal substrate is exposed to obtain a titanium-containing primer nanofilm layer sample.

2. The method for preparing a titanium-containing primer nanofilm sample according to claim 1, characterized in that: The metal substrate comprises a conductive metal or a metal alloy, and the chemical activity of the metal substrate is higher than the chemical activity of the titanium in the titanium-containing bottom nanofilm layer.

3. The method for preparing a titanium-containing primer nanofilm sample according to claim 1, characterized in that: The metal substrate includes at least one of iron, magnesium, aluminum, zinc, tin, manganese, nickel, chromium or an alloy thereof, and the titanium-containing base nanofilm layer includes a single-layer or multi-layer nanofilm layer with titanium or titanium alloy as the base layer.

4. The method for preparing a titanium-containing primer nanofilm sample according to claim 3, characterized in that: The titanium content in the titanium alloy is greater than 30%, and the titanium alloy does not contain other active metals with higher chemical activity than titanium.

5. The method for preparing a titanium-containing primer nanofilm sample according to claim 1, characterized in that: The removing of the metal substrate from the test piece by reaction specifically comprises: dissolving sulfuric acid and sulfate in deionized water to obtain a reaction solution; The metal substrate on the test piece connected to the positive electrode of direct current and attached with the reference sheet is used as an anode, and the platinum electrode connected to the negative electrode of direct current is used as a cathode, and placed in the reaction solution; A voltage is applied between the anode and the cathode, so that the metal substrate reacts with the reaction solution and is dissolved and removed from the test piece.

6. The method for preparing a titanium-containing primer nanofilm sample according to claim 5, characterized in that: The voltage is less than a voltage required for the titanium-containing primer material in the titanium-containing primer nanofilm layer to react with the reaction solution.

7. The method for preparing a titanium-containing primer nanofilm sample according to claim 6, characterized in that: The method of applying voltage between the anode and the cathode specifically includes: setting a range of the voltage, and applying the voltage in a manner of gradually decreasing the voltage value within the range of the voltage during the entire reaction stage, so that the reaction rate of the metal substrate and the reaction liquid decreases from high to low.

8. The method for preparing a titanium-containing primer nanofilm sample according to claim 6, characterized in that: The method for applying a voltage between the anode and the cathode specifically includes: setting a range of the voltage, and applying the voltage in a manner of gradually increasing and then gradually decreasing the voltage value within the range of the voltage during the entire reaction stage, so that the reaction rate of the metal substrate and the reaction liquid increases from low to high and then to low.

9. The method for preparing a titanium-containing primer nanofilm sample according to claim 5, characterized in that: Also includes: During the entire reaction stage, the pH value and sulfate concentration of the reaction solution are analyzed. When the analyzed pH value exceeds a threshold value, sulfuric acid is added to the reaction solution according to a set sulfuric acid concentration range so that the pH value falls within the threshold value again. When the analyzed sulfate concentration exceeds the lower limit of the set sulfate concentration range, sulfate is added to the reaction solution so that the sulfate concentration reaches the median of the set sulfate concentration range or the initial preparation concentration of sulfate.

10. The method for preparing a titanium-containing primer nanofilm sample according to claim 9, characterized in that: The threshold is less than 2.

11. The method for preparing a titanium-containing primer nanofilm sample according to claim 5, characterized in that: The sulfuric acid concentration ranges from 1.5 to 20 g / L, and the sulfate concentration ranges from 5 to 100 g / L.

12. The method for preparing a titanium-containing primer nanofilm sample according to claim 11, characterized in that: The sulfuric acid concentration ranges from 2 to 12 g / L, and the sulfate concentration ranges from 16 to 80 g / L.

13. The method for preparing a titanium-containing primer nanofilm sample according to claim 5, characterized in that: The voltage range is 2-7V, and the current density applied to the anode ranges from 150-700A / m 2 .

14. The method for preparing a titanium-containing primer nanofilm sample according to claim 5, characterized in that: The sulfate includes at least one of sodium sulfate, potassium sulfate and ammonium sulfate.

15. The method for preparing a titanium-containing primer nanofilm sample according to claim 5, characterized in that: The method of tightly fitting the insulating reference plate to the surface of the titanium-containing base nanofilm layer away from the metal substrate specifically includes: tightly bonding the reference plate to the surface of the titanium-containing base nanofilm layer away from the metal substrate by an insulating adhesive, and during the bonding, first evenly applying the adhesive on the surface of the titanium-containing base nanofilm layer, and then bonding the reference plate to the surface of the titanium-containing base nanofilm layer coated with the adhesive, and using the dead weight of the reference plate to tightly fit the reference plate and the test piece; and after the reference plate and the test piece are firmly bonded, placing the test piece in the reaction solution.

16. The method for preparing a titanium-containing primer nanofilm sample according to claim 15, characterized in that: The adhesive comprises glue or instant adhesive; and / or the reference sheet comprises a plastic sheet.

17. The method for preparing a titanium-containing primer nanofilm sample according to claim 5, characterized in that: Also includes: Visually observe, and when the metal substrate is dissolved to the target position, cut off the power supply; Taking the test piece out of the reaction solution and soaking and cleaning it in pure water; The cleaned test piece was air-dried.

18. A titanium-containing bottoming nanofilm layer sample prepared using the method for preparing a titanium-containing bottoming nanofilm layer sample according to any one of claims 1 to 17, wherein the titanium-containing bottoming nanofilm layer sample is used for directly observing and testing the exposed surface of the titanium-containing bottoming nanofilm layer close to the metal substrate retained on the reference film after the metal substrate is reactively removed, and / or for further preparing slice samples.